The use of information technology to improve student’s deep understanding of matter and energy - Martini; Erman; Qosyim, A (Journal of physics. Conference series, 2021)
Advances in information technology make it easy to get a lot of information from internet. Therefore, teachers must facilitate learning that encourages students to increase their deep understanding with the use of information technology. Through the implementation of the PDCA model, which consists of Plan, Do, Check, and Act, students gradually search for information on the topic of material change. The topic which consists of three sub topics, namely: (1) the composition; (2) the electricity; and (3) the magnetism. The subjects in this study were 20 students from the superior class of S1 Science Education. The implementation of the PDCA model is designed as follows, (1) the planning stage, students are given the task of finding information by internet about the sub topics that become their assignments. Students read and understand it; (2) the doing stage, students are asked to describe what is read, and formulate questions from the information read; (3) the checking stage, students re-examine the questions formulated; and (4) the action stage, students look for information to answer the questions in the previous stage. The study was conducted in two cycles. The results were obtained that there was an increase in students’ deep understanding of all sub topics.